ANALISIS DAN PERANCANGAN SISTEM INFORMASI PENJUALAN RUMAH BERBASIS WEB PADA PT. MITRA HASRI - Fadhli, Fadhli; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2017)
System used by the company in dealing with of recording, promotion and sale of home products is stilldone manually thus hindering the performance of the company. With wich the author designed theproposed system can solve these problems while providing a fast house sale information. The use of thisnew system works so that appropriate treatment can be done fast and in the process of selling the houseso as to assist the smooth operation of the company and at the same time improving service to customers.The resulting report form data report home, customer report, marketing home report, periodic paymentreport, home specification and credit simulation